Алгоритм діагностики осетопорозу та оцінка ризику переломів у жінок із цукровим діабетом 2-го типу у постменопаузальний період - Кирилюк, М. Л.; Щекатурова, Л. В.; Третяк, О. Е.; Підаєв, А. В. (Clinical Endocrinology and Endocrine Surgery, 2014)
The article presents the current data regarding diagnostic of osteoporosis at menopausal female with type 2 diabetes and evaluation of fracture risk forecast. The authors recommend that all stages of diagnostic in patients with suspected osteoporosis should be supplemented with osteodestruction marker β-CrossLaps and osteosynthesis marker osteocalcin. Diagnosis should be confirmed by DEXA for all patients.